Свояк Сталіна (сторінки біографії комісара держбезпеки 1 рангу Станіслава Реденса) - Золотарьов, В. (З архівів ВУЧК-ГПУ-НКВД-КГБ, 2004)
The person of S. F. Redense (the head of State Political Office of Ukrainian SSR during 1931–33) still remains the one that passes over in silence. There are some sketches of his biography, but there hasn’t been any scientific investigation of his activity in Russia as well as in Ukraine. The author for the first time made detailed description of the basic phases of S. F. Redence’s life; showed his real role in the creation and administration of Bolshevik’s punitive institutions; ascertained the circumstances of his death.